HUBUNGAN REWARD DAN PUNISHMENT TERHADAP KINERJA PEGAWAI BAGIAN DIVISI KEPEGAWAIAN DI KEMENTRIAN KOPERASI DAN UKM JAKARTA SELATAN - Octaviani, Elisabeth; Sembiring, Carrolina F.; Tampubolon, Emma (Fundamental Management Journal, 2016)
Research conducted at the Ministry of Cooperatives and SMEs in South Jakarta to determine the relationship of reward and punishment to employee performance. To find reward and punishment with the performance of employees in the Ministry of Cooperatives and SMEs in South Jakarta. Data obtained through field research and library research, and the distribution of questionnaires. This research was conducted at the personnel division in the Ministry of Cooperatives and SMEs Jl.H.R.Rasuna Kav.3-4 Said in South Jakarta. The research model used in this study ie the method of literature study, field studies and questionnaires conducted systematically in accordance with the purpose of research. Samples in this study were 21 employees. The analytical method used is the T test (partial) and Spearman rank correlation analysis. The results of this study indicate that the variable reward has a positive relationship with employee performance. This has been proven through the test t, where t test results showed that the t value (2.285)> t table (2,093). And the outcome variables punishment also has a positive relationship with the employee's performance as evidenced by t, where t test results showed that the t value (2.216)> t table (2,093) Of the two independent variables most dominant have a relationship with the employee's performance is reward (X1). Advice writer is a variable reward should be considered again in the offering to employees, so that employees who have competence good performance can receive a reward with justice for what he has given to the company because in this study the variable reward also have a positive relationship to the performance of employees.